ANALISIS LIKUIDITAS DAN PROFITABILITAS UNTUK MENILAI KINERJA KEUANGAN PADA PT. TELEKOMUNIKASI INDONESIA, TBK - Alpius Wenda; Norbertha Ditilebit (ark:/00000/jeb.v11i2, 2021)
The aim of this study ; 1) To analyze the financial performance seen from the level of liquidity and profitability at PT. Telekomunikasi Indonesia, Tbk in 2014-2016. 2) To analyze the development of liquidity and profitability ratios at PT. Telekomunikasi Indonesia, Tbk” in 2014-2016. 3) To analyze the financial performance seen from the level of liquidity and profitability at PT. Telekomunikasi Indonesia, Tbk when compared with industry standards. The results showed that 1). In general, the financial performance of PT. Telekomunikasi Indonesia, Tbk based on the results of the liquidity ratio in the current ratio and quick ratio fluctuating can be said to be good because it is able to fulfill its short-term obligations even though the company has not been able to maximize its current assets and for the profitability ratio results can be said to be good too because it is able to generate profits despite a decrease in profit. margin and fluctuations in Return On Assets, and Return On Equity. 2). The development of the liquidity ratio and profitability of PT. Telekomunikasi Indonesia, Tbk has not been so efficient this is because the development in each liquidity and profitability ratio is not so stable, the result is that there is a decrease and there is also an increase in each current year. The development of liquidity and profitability ratios in 2015 to 2016 includes the liquidity ratio where the current ratio and quick ratio fluctuated while the profitability ratio where profit margin decreased, and Return On Assets fluctuated while Return On Equity increased in 2015 to 2016 Fluctuations in the development of the liquidity ratio occurred because PT. Telekomunikasi Indonesia, Tbk has not been able to minimize current debt and maximize existing current assets, while for the results of the development of profitability ratios a decline can occur because assets are not managed efficiently each year, causing low net income and the company's financial performance is not so good. 3). Comparison of industry standards from the results of the liquidity and profitability ratios of PT. Telekomunikasi Indonesia, Tbk, although able to meet its short-term obligations and generate profits where the current ratio and quick ratio do not meet the standards, while the profit margins meet industry standards, Return On Assets, and Return On Equity do not meet industry standards.